Working in the recicled inner city: insertions and extractions - Castellano-Pulido, Francisco Javier; García Píriz, Tomás (My University, 2017)
The idea of recicled inner city is conceived from its own account as a living heritage in constant transformation that does not depend on a deliberate formal strategy but on the intertwining time, materials and activities. In the last fifteen years we have studied its many forms and scales through our own work of constructing sites and projects. These projects assume that the activity builds different cities at all times: superimposed cities, running in parallel, continuously enriched. In this sense we can highlight two of our proposals that can clearly reflect this way of understanding the act of recycling the European city, both of them located in Granada (Spain): The first one, Atelier in San Jerónimo street, is a cheap intervention, our own architectural atelier. On a small scale, we propose a course of action based on recycling material and symbolic of a collection of fragments of the city that are physically and conceptually displaced within an old premises (a mortuary and a parlour afterwords). The second one, Babydog Office, is an advertising office inserted in an old building in which the existing brick loading walls are cut, forming, through the reflections, an infinite interior landscape of discharge arcs.
Keywords: Rehabilitación urbana; Reutilización; Patrimonio; Arquitectura; Diseño interior; Reciclaje urbano; Oficinas